The EMG of conventional abdominal exercise and exercise with a semi-upright commercial device: comparative effects and technique considerations - Olson, M. S.; Esco, M. R.; Williford, H. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The purpose of this study was to measure and compare the muscle activity of the rectus abdominis (RA) and external obliques (EO) with conventional exercises and while using an upright commercial abdominal training device (the CoreMaster). It was hypothesized that the upright device would elicit higher electromyography (EMG) values compared to conventional abdominal exercises. Methods. Fifteen subjects (8 males, 7 females) participated in this study. Each subject performed 10 repetitions for 5 exercises: truck lift (TL); trunk rotation to opposite knee (TROK); trunk lift on the CoreMaster (TLCM); trunk rotation on the CoreMaster (TRCM); and trunk rotation with a leg lift on the CoreMaster (TRLLCM). Muscle activity was measured for the RA and EO using surface EMG. A Biopac system (Goleta, CA, USA) processed the EMG signals. A repeated measures analysis of variance (ANOVA) determined any difference in the root mean square values and Bonferroni comparisons were used to clarify the order of differences (P<0.05). Results. For the RA, all exercises on the CoreMaster produced significantly higher EMG values compared to the conventional TL. For the EO, TRCM elicited the highest EMG values. However, no significant difference was found for EO between TROK and TRLLCM. Conclusion. The CoreMaster elicited a greater challenge to the RA. For the EO, the CoreMaster yielded optimal effects for exercises that required pronounced rotation.